2018
DOI: 10.1063/1.5049341
|View full text |Cite
|
Sign up to set email alerts
|

A computer model and methodology to predict temperatures and deformations during diamond multi-wire cutting

Abstract: Analysis of structured wire wafering processes to predict optimized process settings by varying particle size and wire diameter AIP Conference Proceedings 1999, 140001 (2018) Abstract. The Diamond wire slicing process for multi-Si wafering is relatively new, and there are limited threedimensional thermal field simulations in this area. This work aims to fill the gap by using a Finite-Element model to simulate this complex mechanical-thermal process where the wires and wafers are continuously working in a therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…While it was shown that the coolant has a significant effect on the wafer temperature field [12], temperatures in the contact zone are typically much higher than the boiling temperature and therefore have little effect on the temperature in the cutting zone [13]. Lindholm et al [14] have studied the coolant temperature rise during wire sawing of multi-crystalline silicon and have simulated the temperature change during the cut along with the resulting effects of thermal expansion. Depending on the cooling conditions, the heat generation between the wires and the silicon block has been determined to lie between 0.28 and 0.43 W/mm, leading to temperatures in the material of up to 270 • C in the beginning of the cut.…”
Section: Introductionmentioning
confidence: 99%
“…While it was shown that the coolant has a significant effect on the wafer temperature field [12], temperatures in the contact zone are typically much higher than the boiling temperature and therefore have little effect on the temperature in the cutting zone [13]. Lindholm et al [14] have studied the coolant temperature rise during wire sawing of multi-crystalline silicon and have simulated the temperature change during the cut along with the resulting effects of thermal expansion. Depending on the cooling conditions, the heat generation between the wires and the silicon block has been determined to lie between 0.28 and 0.43 W/mm, leading to temperatures in the material of up to 270 • C in the beginning of the cut.…”
Section: Introductionmentioning
confidence: 99%